Legal Normativity in Novel Technology of Virtual Reality in Universal Gravatar - Sima Hatami; Fathollah Rahimi; Ehsan Aghamohammad aghaee (حقوق فناوریهای نوین)
Artificial intelligence (AL) is advancing without any predictions in technological development and scope. Meanwhile, some legal issues related to the avatar of a real person in Metaverse are discussed here. Considering, the emergence of the metaverse is developing, and all are members Gravatar, therefore, the inclusion of rights and duties in the relationship between them is undeniable, which includes the rights related to Gravatar in the regulation of relationships between them. The first part of the article deals with what rights and duties the metaverse and avatars face in artificial intelligence and basically why the rights of such avatars should be protected. In addition, the integration techniques for giving legal personality to avatars in the metaverse and some damages Such as committing crimes of theft, forgery and abuse of rights in the meantime are criticized. In addition, with an analytical and descriptive approach, imposing responsibility and liabilities on a real person by applying the rule of piercing veil" in the form of corporate law regarding avatars in terms of identifying the real natural person behind the avatar and through the criminalization of predictable actions and activities as the final result in applying the company's rights and the punishment applicable to the legal personality has been reviewed.